(2S*,4S*)-4-[(E)-(2,2-Dimethylhydrazono)methyl]-6-methoxy-4-methyl-2-[(E)-styryl]-1,2,3,4-tetrahydroquinoline - José Clerigué; M. Teresa Ramos; J. Carlos Menéndez (Molbank, 2021)
The Povarov reaction of p-anisidine, cinnamaldehyde and methacrolein dimethylhydrazone afforded a 1,2,3,4-tetrahydroquinoline derivative bearing 2-styryl, 4-methyl and 4-dimethylhydrazono substituents in a fully diastereoselective fashion. This is the first example of the combination of a type I aza-vinylogous Povarov reaction and a type II vinylogous Povarov reaction in the same process.